2016
DOI: 10.1007/s10646-016-1724-9
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale monitoring of effects of clothianidin dressed oilseed rape seeds on pollinating insects in Northern Germany: implementation of the monitoring project and its representativeness

Abstract: Monitoring studies at the landscape level are complex, expensive and difficult to conduct. Many aspects have to be considered to avoid confounding effects which is probably the reason why they are not regularly performed in the context of risk assessments of plant protection products to pollinating insects. However, if conducted appropriately their contribution is most valuable. In this paper we identify the requirements of a large-scale monitoring study for the assessment of side-effects of clothianidin seed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Agricultural soils are therefore often contaminated with multiple pesticides (Hvě zdová et al 2018). Measurable neonicotinoid residues in various crop soils range from 10 −1 to 10 1 ng/g (Jones et al 2014;Botías et al 2015;Heimbach et al 2016;Wood and Goulson 2017). To assess pesticide exposure, it is important to know not only the (peak) concentrations but also the persistence in the soil matrix.…”
Section: Soilmentioning
confidence: 99%
“…Agricultural soils are therefore often contaminated with multiple pesticides (Hvě zdová et al 2018). Measurable neonicotinoid residues in various crop soils range from 10 −1 to 10 1 ng/g (Jones et al 2014;Botías et al 2015;Heimbach et al 2016;Wood and Goulson 2017). To assess pesticide exposure, it is important to know not only the (peak) concentrations but also the persistence in the soil matrix.…”
Section: Soilmentioning
confidence: 99%
“…An example of the requirements of large field studies and their implementation is given by Heimbach et al ( 2016 ). A wider review of neonicotinoid field studies by the industry can be found in Schmuck and Lewis ( 2016 ).…”
Section: Part A: Invertebratesmentioning
confidence: 99%
“…The study investigated the amount of pesticide residues in the nectar and honey, the composition of pollen collected by bees, the potential adverse effects on bumble bees and bees, the strength and development of colonies, and honey production. The findings revealed no adverse effects on these insects (Heimbach et al, 2016;Rolke et al, 2016;Schmuck, Lewis, 2016;Sterk et al, 2016). A similar study conducted in Estonia in 2013-2014 by Karise et al (2017) found that the concentration of all pesticide residues was lower than the lethal dose for honey bees.…”
Section: Introductionmentioning
confidence: 56%